Performance test of a fully differential float-glass multi-strip MRPC prototype for the CBM ToF wall with cosmic rays - Simon, Christian; Deppner, Ingo Martin; Herrmann, Norbert; Loizeau, Pierre-Alain; Frühauf, J. (Journal of Instrumentation, 2014)
A full-size float-glass MRPC prototype for the peripheral part of the time-of-flight (ToF) wall of the future Compressed Baryonic Matter (CBM) experiment is presented. In a cosmic-ray test, a time resolution of 40 ps (including contributions from discrimination and digitization electronics) was observed. The detection efficiency was found to be above 98 %. In these respects, the MRPC prototype surpasses the criteria formulated by the CBM collaboration. The analysis algorithm applied to the MRPC raw data is described in detail clustering correlated MRPC hits and correcting for various dependencies.
Gesehen am 04.09.2020